POLA PERILAKU THOMAS LANGUR (Presbytis thomasi, Collect 1892) DI SEKITAR HUTAN LARANGAN ADAT RUMBIO - Mukhtar, Ade; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The problem of  Thomas langur occur arround of Hutan Larangan Adat Rumbio one of them is Thomas langur entering the lovihood zone of society dan attck the palnt arround of society. This is disturb the activity that causes harm like reduce of productivity of palnt. This reseacrh doing at February-March 2015 in Hutan Larangan Adat Rumbio. The method that used in this research is Observe on Partisipant, snowball sampling. The daily habit of  Thomas Langur as long as period of research start from 06-08 o’clock include of the habot of eat (56,7%), take a rest (10,2%), grooming (22,1%), and playing (11%). The interaction of Thomas langur with society arround of  Hutan Larangan Adat Rumbio causes harm that occur by the society like failed to the harvest of rubber, fruits and the tools of plant of society. Key words: Thomas langur, Hutan Larangan Adat Rumbio, Pola Perilaku Thomas